PENYULUHAN DIGITAL MARKETING DAN PENGELOLAAN KEUANGAN SEDERHANA UNTUK UMKM DI DESA CIKURUTUG KECAMATAN CIREUNGHAS - Sugih Prakoso (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Cikurutug Village shows quite a large potential, especially for domestic companies that have not been fully optimized in their management practices. This situation arises from the relatively limited education of the community, because most of the residents in Cikurutug Village work as laborers, farmers, and some people operate home-based businesses, including bamboo crafts, snack production, and brown sugar farmers. In their efforts to increase productivity, the residents of Cikurutug Village currently lack knowledge related to digital-based sales. Therefore, the purpose of this community service initiative is to provide counseling on digital marketing for MSMEs in Cikurutug Village. The methods used in this training activity are lecture and discussion methods. The lecture method is used to explain topics related to simple financial management and digital marketing strategies. Furthermore, discussions are held to enrich the discourse on the material presented, including individual questions and representative questions from the participants. The results of the counseling initiative showed a very high level of enthusiasm from the participants, who were involved in home-based entrepreneurship in Cikurutug Village. This enthusiasm was proven by the many questions asked by participants regarding the procedure for creating an account on the market place platform, where the facilitator tried to respond and provide a comprehensive explanation of the topic raised.